The Dynamics of the Number of Firms in an Industry - Howrey, E. P.; Quandt, R. E. (Review of Economic Studies, 1968)
E. P. Howrey, R. E. Quandt; The Dynamics of the Number of Firms in an Industry1, The Review of Economic Studies, Volume 35, Issue 3, 1 July 1968, Pages 349